Dermal uptake and percutaneous penetration of organophosphate esters in a human skin ex vivo model. (April 2018) - Frederiksen, Marie; Stapleton, Heather M.; Vorkamp, Katrin; Webster, Thomas F.; Jensen, Niels Martin; Sørensen, Jens Ahm; Nielsen, Flemming; Knudsen, Lisbeth E.; Sørensen, Lars S.; Clausen, Per Axel; Nielsen, Jesper B.
Abstract: Organophosphate esters (OPEs) are used as flame retardants, plasticizers, and as hydraulic fluids. They are present in indoor environments in high concentrations compared with other flame retardants, and human exposure is ubiquitous. In this study we provide data for estimating dermal uptake for eight OPEs and ranking in OPEs risk assessment. Dermal uptake and percutaneous penetration of the OPEs were studied in a Franz diffusion cell system using human skin dosed with a mixture of OPEs in an ethanol:toluene (4:1) solution. Large variation in penetration profiles was observed between the OPEs. The chlorinated OPEs tris(2-chloroisopropyl) phosphate (TCIPP), and in particular tris(2-chloroethyl) phosphate (TCEP), penetrated the skin quite rapidly while tris(1, 3-dichlor-2-propyl) phosphate (TDCIPP) and triphenyl phosphate (TPHP) tended to build up in the skin tissue and only smaller amounts permeated through the skin. For tris(isobutyl) phosphate (TIBP), tris(n-butyl) phosphate (TNBP), and tris(methylphenyl) phosphate (TMPP) the mass balance was not stable over time indicating possible degradation during the experimental period of 72 h. The rates at which OPEs permeated through the skin decreased in the order TCEP > TCIPP ≥ TBOEP > TIBP ≥ TNBP > TDCIPP > TPHP > TMPP. Generally, the permeation coefficient, kp, decreased with increasing log Kow, whereas lag time and skin deposition increased with log Kow . The present data indicate that dermal uptake is a non-negligible human exposure pathway for the majority of the studied OPEs. Graphical abstract: Image 1 Highlights: Dermal uptake of organophosphate esters (OPEs) were determined. TCEP is transported fastest of the studied OPEs across the skin. Dermal uptake decreased with increasing log Kow . Skin deposition increased with increasing log Kow . Dermal absorption is an important exposure pathway for OPEs.